Cotranslational membrane insertion of the voltage-sensitive K + channel KvAP - Justin M. Westerfield; Petra Kozojedová; Cara Juli; Ane Metola; Gunnar von Heijne (Proceedings of the National Academy of Sciences, 2025)
Voltage-sensor domains (VSDs), found in many voltage-sensitive ion channels and enzymes, are composed of four transmembrane helices (TMHs), including the atypical, highly positively charged S4 helix. VSDs are cotranslationally inserted into the membrane, raising the question of how the highly charged S4 helix is integrated into the lipid bilayer as it exits the ribosome. Here, we have used force profile analysis (FPA) to follow the cotranslational insertion of the six-TMH KvAP voltage-sensitive ion channel into the Escherichia coli inner membrane. We find that the insertion process proceeds through three semi-independent steps: i) insertion of the S1-S2 helix hairpin, ii) insertion of the S3-S5 helices, and iii) insertion of the Pore and S6 helices. Our analysis highlights the importance of the concerted insertion of helical hairpins, the dramatic influence of the positively charged residues in S4, and the unexpectedly strong forces and effects on downstream TMHs elicited by amphipathic and re-entrant helices.